Late Romantic Reflections by Valentin Bibik - Mizitova, Adilya; Ivanova, Irina (Journal of History Culture and Art Research, 2020)
The article considers the ways of recreating the stylistic properties of late romanticism in the symphonies of the Ukrainian composer V. Bibik (1940–2003). The master’s openness to contacts with various national cultures manifested itself in the circumstances of his life and in the breadth of artistic interests, among which the musical traditions of late romanticism occupied a special place. The affinity of V. Bibik’s composing individuality to the romantic worldview is confirmed by the emphasis on the personality beginning, the monologue nature of the utterance, the sharpness of the reaction to the dissonances of life. Neo-romantic tendencies in the art of music of the last third of the last century stimulated the “meeting” of the modern Ukrainian author with the spiritual and aesthetic heritage of the 19th century. The path traversed by V. Bibik in this direction reflects the gradual maturation of the composer’s creative dialogue with the heritage of the previous culture: from the first obvious responses to late romanticism in the Fifth Symphony, through the testing of its recognizable features on the national-Ukrainian material in the vocal Sixth Symphony to the poems by T. Shevchenko to a kind of “triptych” of symphonic concepts of the Seventh – the Eighth – the Ninth. In them, stylistic signs of late romanticism cover all levels of artistic structure (spiritual, meaningful, dramaturgic, compositional, form-building, and thematic). At the same time, the composer is not engaged in modelling certain genre, stylistic parameters, but transforms the borrowed musical realities into signs, including them into his own ideological imaginative concept. As a result, they turn from “strangers” into “friends”, organically entering the individual stylistic context of the author. The constancy of V. Bibik’s artistic and aesthetic reference points can be judged by the author’s subsequent unnumbered Symphonies to the texts by M. Tsvetaeva and J. Brodsky, respectively. Their performing group – a vocal solo and a symphony orchestra – refers to the late romantic experiments of creating a special genre variety: the orchestral vocal cycle.